TLR2 Activation as a Marker of Severe COVID-19 and a Potential Therapeutic Target - Mao, Xianxian; Wu, Yijia; Zhang, Xinyi; Zhou, Tian; Huang, Houda; Fu, Mingui; Qian, Yisong (Current Medicinal Chemistry, 2025)
SARS-CoV-2-induced COVID-19 has been a serious public health problem, resulting in millions of lives lost over the previous three years. Although the direct infection caused by virus invasion is important for the pathobiology of COVID-19, the hyperinflammatory response and tissue injury are major contributors in critically ill patients. As a host sensor, toll-like receptor 2 (TLR2) recognizes multiple pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs), producing various inflammatory cytokines and inflammatory cell death signals, which are central to the inflammatory pathology observed in COVID-19. The objectives of this narrative review are to summarize the role of TLR2 activation during SARS-CoV-2 infection and emphasize the importance of SARS-CoV-2 viral proteins in TLR2 activation. Additionally, we presented some compounds related to TLR2 regulation clinically or experimentally, which may provide new insights into targets for pharmaceutical discovery and development.
Keywords: inflammatory response